Developments in Hospitality Marketing and Management: Social Network Analysis and Research Themes - Nunkoo, R.; Gursoy, D; Ramkissoon, H. (2013)
Academic journals, with their rigorous peer-review process, play a central role in the scientification of knowledge. However, researchers and scholars often fail to appreciate and understand the black box of such agents of knowledge production. Using content analysis of articles published in the two most recent volumes of Journal of Hospitality Marketing and Management, this article attempts to shed some lights on the nature of knowledge in hospitality studies. The results indicated that research is highly concentrated in the developed world, while the voices of developing nations are marginalized. This pattern provides some indication of underlying power dimensions in the production of hospitality knowledge. A social network analysis of contributors indicated that hospitality research is largely the product of collaborative efforts among members of the scientific community. Collaboration among researchers from the same country was the most common form of networking. In terms of research areas, the behaviors of travelers and consumers of hospitality and tourism services were well-studied among scholars.